A 3D-printed biomaterials-based platform to advance established therapy avenues against primary bone cancers. (December 2020) - Lahr, Christoph A.; Landgraf, Marietta; Sanchez-Herrero, Alvaro; Dang, Hoang Phuc; Wagner, Ferdinand; Bas, Onur; Bray, Laura J.; Tran, Phong; Holzapfel, Boris M.; Shafiee, Abbas; McGovern, Jacqui A.; Hutmacher, Dietmar W.
Abstract: In this study we developed and validated a 3D-printed drug delivery system (3DPDDS) to 1) improve local treatment efficacy of commonly applied chemotherapeutic agents in bone cancers to ultimately decrease their systemic side effects and 2) explore its concomitant diagnostic potential. Thus, we locally applied 3D-printed medical-grade polycaprolactone (mPCL) scaffolds loaded with Doxorubicin (DOX) and measured its effect in a humanized primary bone cancer model. A bioengineered species-sensitive orthotopic humanized bone niche was established at the femur of NOD-SCID IL2Rγ null (NSG) mice. After 6 weeks of in vivo maturation into a humanized ossicle, Luc-SAOS-2 cells were injected orthotopically to induce local growth of osteosarcoma (OS). After 16 weeks of OS development, a biopsy-like defect was created within the tumor tissue to locally implant the 3DPDDS with 3 different DOX loading doses into the defect zone. Histo- and morphological analysis demonstrated a typical invasive OS growth pattern inside a functionally intact humanized ossicle as well as metastatic spread to the murine lung parenchyma. Analysis of the 3DPDDS revealed the implants' ability to inhibit tumor infiltration and showed local tumor cell death adjacent to the scaffolds without any systemic side effects. Together these results indicate a therapeutic and diagnostic capacity of 3DPDDS in an orthotopic humanized OS tumor model. Graphical abstract: Image, graphical abstract